Predictive maintenance of HVAC system using supervised machine learning algorithms - Fahim, Md. Zubayer Ahmed; Roy, Tiash; Rakib, Mma; Sharar, Shihab (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.